Analysis of the effectiveness of physical education instruction as viewed through teachers’ instructional skills - Greciella Baby Regina Listiono Putri; Bayu Budi Prakoso; Fifukha Dwi Khory; Suroto Suroto; Vega Candra Dinata (Sriwijaya Journal of Sport, 2026)
Research Problems: Research on physical education teachers’ instructional skills has primarily focused on general teaching behaviors and has not specifically examined instructional monitor during classroom instruction. Research Objectives: This study aims to analyze the relationship between teachers’ instructional skills and the effectiveness of Physical Education, Sports, and Health (PJOK) learning in elementary schools. Methods: This study employed a quantitative correlational approach involving 17 PE teachers from 15 elementary schools in Surabaya, Sidoarjo, and Gresik selected through convenience sampling. Data were collected using a teacher instructional skills observation sheet and a Formative Class Evaluation (FCE) questionnaire. Data were analyzed using linear regression with a Percentile Bootstrap approach involving 1,000 resamples at a 95% confidence level. Results: The results showed that instructional monitor skills were significantly associated with motivation, teaching methods, and overall learning effectiveness (p < 0.05). In contrast, the skill of providing initial instructions was not significantly associated with any indicators of learning effectiveness. Conclusion: These findings indicate that the effectiveness of PJOK learning is more closely related to teachers’ ability to monitor learning activities, conduct active observations, and provide feedback throughout the learning process rather than merely delivering clear initial instructions. This study highlights the importance of developing instructional monitor competencies in PE teacher training programs to enhance student engagement and learning experiences.